Halloween safety - Alden, Laura, 1955-; McCallum, Jodie (Chicago : Childrens Press, 1993)
Joey and Rachel enjoy trick-or-treating on Halloween and almost lose their bags of goodies.
2.2
K-3
Keywords: Halloween -- Fiction; Halloween -- Fiction